Policy Implication and Research on Preschool Education and Its Lasting Effect: Examining the Impact of Preschool Education on Student Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The purpose of this study was to determine if a difference in achievement scores exist between students who attended the School System preschool program and those who did not as measured by standardized achievement test Reading/Language Arts and Math scores of students in the third and fourth grades. The variables of grade level and preschool attendance were considered. The population consisted of students who were in the third or fourth grades in the School System during the 2010-2011 school years through the 2012-2013 school years. Independent and paired t-tests were used to evaluate differences in the variables. The investigation of the relationship between attendance in preschool and achievement test scores might assist educators in planning and implementation of future preschool programs within the public school setting.